Managing the health and productivity of HLB-affected groves - Tripti Vashisth (EDIS)
In 2005, Huanglongbing (HLB) or citrus greening disease was first discovered in Florida. Florida orange production changed from 242 million boxes (90 lbs/box) in the pre-hurricane, pre-HLB, 2003-04 season to 81.5 million boxes in 2015-16. This dramatic reduction in yield is attributable to multiple causes, including a reduction in citrus acreage, citrus canker and other citrus diseases. HLB is now recognized as the primary reason for declining citrus yields. Growers are urgently looking for strategies to maintain fruit production in their groves under endemic HLB conditions.